2004
DOI: 10.1016/j.ejvs.2004.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Is Ultrasound More Accurate than Axial Computed Tomography for Determination of Maximal Abdominal Aortic Aneurysm Diameter?

Abstract: Compared to axial CT, US is a better approximation of true perpendicular AAA diameter as determined by orthogonal CT. When aortic angulation is greater than 25 degrees axial CT becomes unreliable. However, US measurements are not affected by angulation and agree strongly with orthogonal CT measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 16 publications
5
66
0
2
Order By: Relevance
“…The duplex scan has emerged as the most practical method for the screening and follow-up of infrarenal abdominal aortic aneurysms, while computed tomography is considered to be the gold standard. Several authors have noted a difference between abdominal aortic diameter measurements obtained with duplex ultrasound and those obtained with computed tomography [8][9][10][11][12][13][14]. Despite frequently noted discrepancies, these issues have not been adequately addressed in the literature, and in only a few studies has a direct comparison of aortic diameters using duplex and computed tomography been performed [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…The duplex scan has emerged as the most practical method for the screening and follow-up of infrarenal abdominal aortic aneurysms, while computed tomography is considered to be the gold standard. Several authors have noted a difference between abdominal aortic diameter measurements obtained with duplex ultrasound and those obtained with computed tomography [8][9][10][11][12][13][14]. Despite frequently noted discrepancies, these issues have not been adequately addressed in the literature, and in only a few studies has a direct comparison of aortic diameters using duplex and computed tomography been performed [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…19 Additionally, ultrasonography is also able to provide a better approximation to the true perpendicular diameter of an abdominal aortic aneurysm, since it is not affected by the angle of the aorta, which impacts on tomography results at angles greater than 25°. 20 Endoleaks can be detected by ultrasound using color spectral analysis to show blood flow. While published specificity rates for detection of endoleaks with Doppler ultrasonography are high (89%-97%), 21 the sensitivity and diagnostic power of Doppler US for detecting endoleaks is still debatable, when compared with angiotomography.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported using duplex ultrasound (Dalainas et al, 2006;Manning et al, 2009). Sprouse et al (2004) suggested that ultrasound is more accurate than axial CT in determining the true perpendicular diameter. This was based on use of orthogonally reconstructed CT, which varied insignificantly from US, while axial CT overestimated the diameter when the aortic angulation was high.…”
Section: Detection and Monitoringmentioning
confidence: 99%